La decisión fiscal de actuar solo diligencias pertinentes y su impacto en principios constitucionales en el Distrito Judicial de Loreto 2025 - Cambero Alva, Jorge Walter (2025)
This research corresponds to a non-experimental design, with a quantitative approach and a non-descriptive level. The study population is made up of a sample of twenty (20) legal professionals including judges, prosecutors and defense attorneys - public and private - who administer justice and exercise defense before the courts of the Judicial District of Loreto in criminal matters; the survey technique and a questionnaire were used as an instrument. This research has verified through the results obtained that the prosecutor's decision to act only the proceedings it considers pertinent affects the constitutional principles of the corresponding trial, effective jurisdictional protection, the right to promote evidence and the right of defense in the Judicial District of Loreto during 2025, as shown in Table No. 7. The data were statistically analyzed using Spearman's correlation coefficient for the non normality of a variable. The results showed a high positive and significant correlation (ρ = 0.778; p < 0.001) between discretion, coupled with fiscal objectivity and the violation of constitutional principles, therefore, the hypothesis is accepted that acting only in proceedings considered pertinent violates principles such as due process, effective jurisdictional protection, the right to promote evidence and the right of defense in the Judicial District of Loreto in 2025. It is concluded that the current wording of article 337 °.4 of the Criminal Procedure Code facilitates arbitrariness and affects procedural fairness, recommending its review to guarantee a fair criminal process that respects human rights.